PENINGKATAN KREATIFITAS GURU DALAM MEMBUAT VIDEO PEMBELAJARAN INTERAKTIF DI SLB N 2 DENPASAR - Darmawan, I.D.M.B.A.; Astuti, L.G.; Supriana, I.W.; Raharja, M.A. (Buletin Udayana Mengabdi, 2023)
The challenge for teachers in the Covid-19 Pandemic condition which requires learning to be done online is to make good interactions between Teachers and Learners during the learning process. Uneven internet access is an obstacle in implementing live virtual learning (live session) via video conferencing. However, the delivery of material must still be done not only through text media which tends to be more difficult to understand than direct descriptions. The solution offered in the service activities that have been carried out is to introduce the form of asynchronous learning objects in the form of Learning Videos. Making learning videos has challenges so that during the video the attention of the students is not lost. Training on making learning videos has been carried out for high school teachers. The ability to absorb training materials varies, this can be influenced by educational background, mastery of technology and even the age of the participants. Keywords: Learning Videos, Learning Objects, Online, Elearning, SLB